Persistence and interdependence of macroeconomic variables in the West African Monetary Zone - Eshun, Richard (My University, 2020)
The introduction of monetary integration which enables member countries to adopt a common currency is not something which has just been discovered, For example, the Euro is used by the Eurozone as their regional currency; some francophone countries in Africa use the African Financial Community, which is the CFA Franc. Economic Community of West African States desire to introduce a common currency in the sub region has been in the offing since the birth of the regional integration body. This was considered expedient given the fact that there exist in the sub region one of the oldest monetary union which is the Union économique et monétaire ouestafricaine. In 2000, certain countries that belong to the Economic Community of West African States announced their intention to form a second monetary zone by creating the West African Monetary Zone. For the West African Monetary Zone to introduce a common currency, member countries are to fulfill some primary as well as some secondary criteria set up in the macroeconomic convergence criteria. Among some of the primary and secondary criteria are: inflation rate should be single-digit at the end of each year. Member countries are to ensure a stable real exchange rate as well as ensuring a positive real interest rate. The overarching aim of this study is to assess the degree of integration of interest rate, inflation rate and exchange rate in the West African Monetary Zone and to analyse whether convergence as a prerequisite condition for the implementation of the common currency is achievable. The study used a multi-criteria approach to examine the introduction of a single currency. This study used two approaches; the first approach which is Autoregressive Fractionally Integrated Moving Average and Fractionally Integrated Generalized Autoregressive Conditional Heteroskedasticity is used to test the degree of relationship of the macroeconomic variables, that is, interest rates, inflation rates and exchange rates independently and simultaneously in the West African Monetary Zone. The second approach which is wavelet-based methodology is used to test how the variables co-move independently and simultaneously across the West African Monetary Zone. From the study, when there is a shock to any of the macroeconomic variables across the zone, its reversion to the mean varies and again the speed at which it returns to the mean varies as well whiles on the interdependence of the macroeconomic variables across the zone, the study shows that the overall correlations of the three macroeconomic variables are weak both in the short, medium and long term. The evidence suggests that the zone is not ready to establish a monetary integration. Furthermore, from this study, if the zone wants to introduce a single currency for the entire region, it should be done in phases with countries that exhibit high similarities whiles the rest follow gradually as and when they achieve the convergence criteria.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management by Research to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Monetary integration; Macroeconomic; West African Monetary Zone; SDG-8: Decent work and economic growth